Physical fitness reference standards in fibromyalgia: The al‐Ándalus project. (17th October 2016) - Álvarez‐Gallardo, I. C.; Carbonell‐Baeza, A.; Segura‐Jiménez, V.; Soriano‐Maldonado, A.; Intemann, T.; Aparicio, V. A.; Estévez‐López, F.; Camiletti‐Moirón, D.; Herrador‐Colmenero, M.; Ruiz, J. R.; Delgado‐Fernández, M.; Ortega, F. B.
Abstract : We aimed (1) to report age‐specific physical fitness levels in people with fibromyalgia of a representative sample from Andalusia; and (2) to compare the fitness levels of people with fibromyalgia with non‐fibromyalgia controls. This cross‐sectional study included 468 (21 men) patients with fibromyalgia and 360 (55 men) controls. The fibromyalgia sample was geographically representative from southern Spain. Physical fitness was assessed with the Senior Fitness Test battery plus the handgrip test. We applied the Generalized Additive Model for Location, Scale and Shape to calculate percentile curves for women and fitted mean curves using a linear regression for men. Our results show that people with fibromyalgia reached worse performance in all fitness tests than controls ( P  < 0.001) in all age ranges ( P  < 0.001). This study provides a comprehensive description of age‐specific physical fitness levels among patients with fibromyalgia and controls in a large sample of patients with fibromyalgia from southern of Spain. Physical fitness levels of people with fibromyalgia from Andalusia are very low in comparison with age‐matched healthy controls. This information could be useful to correctly interpret physical fitness assessments and helping health care providers to identify individuals at risk for losing physical independence.